Novel antiviral approaches for Marburg: a promising therapeutics in the pipeline - Srivastava, Shriyansh; Kumar, Sachin; Ashique, Sumel; Sridhar, Sathvik Belagodu; Shareef, Javedh; Thomas, Sabin (Frontiers in Microbiology, 2024)
Marburg virus disease (MVD) presents a significant global health threat, lacking effective antivirals and with current supportive care offering limited therapeutic options. This mini review explores the emerging landscape of novel antiviral strategies against MVD, focusing on promising therapeutics currently in the development pipeline. We delve into direct-acting antiviral approaches, including small molecule inhibitors targeting viral entry, replication, and assembly, alongside nucleic acid antisense and RNA interference strategies. Host-targeting antivirals are also considered, encompassing immune modulators like interferons and cytokine/chemokine modulators, broadspectrum antivirals, and convalescent plasma and antibody-based therapies. The paper then examines preclinical and clinical development for the novel therapeutics, highlighting in vitro and in vivo models for antiviral evaluation, safety and efficacy assessments, and the critical stages of clinical trials. Recognizing the challenges of drug resistance and viral escape, the mini review underscores the potential of combination therapy strategies and emphasizes the need for rapid diagnostic tools to optimize treatment initiation. Finally, we discuss the importance of public health preparedness and equitable access to these promising therapeutics in achieving effective MVD control and global health security. This mini review presents a comprehensive overview of the burgeoning field of MVD antivirals, highlighting the potential of these novel approaches to reshape the future of MVD treatment and prevention.